Mortality as the primary constraint to enhancing nutritional and financial gains from poultry: A multi-year longitudinal study of smallholder farmers in western Kenya - Otiang, E.; Campbell, Zoë A.; Thumbi, Samuel M.; Njagi, L.W.; Nyaga, P.N.; Palme, G.H. (Public Library of Science, 2020)
Background